Pelatihan Pembuatan Saus Tomat - Denny Akbar Tanjung; Dewi Nur Anggraeni (Universitas Medan Area, 2019)
Sauce is a complementary food, this food is usually coupled with fried foods, soupy foods and can also be used as a seasoning. Sauce made from tomatoes (if tomato sauce) is blended until smooth and cooked while adding spices to make it taste savory. The sauce's delicacy depends on the freshness of the fruit used, the right spice composition and the correct manufacturing procedure. Sauce in the market often does not include the composition of ingredients and food additives (BTM) such as food preservatives used not to mention we do not know the freshness of fruit and BTM doses added and the manufacturing procedures that are not necessarily clean and do not attach permits granted from the government . Fruits that are not fresh (rotten), doses of food additives (preservatives) added can cause various diseases in the body. Through this community service activity, it is expected that students can make their own tomato sauce by using fresh tomatoes, spices with the right amount and not using preservatives that are harmful to health. By making your own tomato sauce, besides being guaranteed cleanliness and health for your body, you can also save on spending money and be able to become skills for students to become entrepreneurs by producing home-made tomato sauce. In this community service activity there were 2 sessions conducted, the first was counseling about the danger of preservatives in food. The second session, the practice of making tomato sauce using fresh tomatoes, the right dosage of seasoning without using preservatives